Analyzing The Potato Supply Chain In The Modoinding District, South Minahasa Region - Waney, Nordy F. L.; Pakasi, Caroline B. D.; Lolowang, Tommy F. (Jurnal Agroekoteknologi Terapan (JAT), 2026)
This study analyzes the structure and marketing performance of the potato supply chain in Modoinding District, North Sulawesi, Indonesia, with emphasis on product, financial, and information flows across dominant marketing channels. Primary data were collected through structured questionnaires, semi-structured interviews, direct observations, and focus group discussions with farmers and key marketing actors. Supply chain mapping was used to identify actors and channel pathways, while marketing performance was evaluated using marketing margins, marketing costs, marketing profits, and farmer share. The mapping results indicate three dominant channels: (1) local marketing to Modoinding and Kotamobagu traditional markets, (2) distribution to Manado traditional markets, and (3) inter-island distribution via port-based traders/offtakers. Farm-gate price was IDR 15,000/kg across channels, while terminal prices increased with channel length: IDR 17,000–17,500/kg (Modoinding local), IDR 18,500/kg (Kotamobagu), IDR 21,000/kg (Manado), and IDR 25,000/kg (inter-island). Consequently, total marketing margins rose from IDR 2,000–2,500/kg in the shortest channel to IDR 10,000/kg in the inter-island channel, and farmer share declined from approximately 85.7–88.2% (local Modoinding) to 60.0% (inter-island). Transport and shipping-related activities were the main cost drivers in longer channels. Overall, improving postharvest handling, logistics coordination, and market information feedback to farmers is critical to reduce losses and enhancing upstream value capture. Keywords: farmer share; inter-island trade; marketing channels; marketing margin; modoinding District; potato; supply chain mapping